Eye movement desensitization and reprocessing for the treatment and early intervention of trauma among first responders: A systematic review. Issue 3 (22nd January 2022) - Morris, Heather; Hatzikiriakidis, Kostas; Savaglio, Melissa; Dwyer, Jenny; Lewis, Catrin; Miller, Robyn; Skouteris, Helen
Abstract: First responders are exposed to repetitive work‐related trauma and, thus, are at risk of developing posttraumatic stress disorder (PTSD). Eye‐movement desensitization and reprocessing (EMDR) is a psychotherapy intervention designed to treat symptoms of posttraumatic stress. We conducted a systematic review to examine the viability of EMDR among first responders. The primary aim of this review was to identify studies that have trialed EMDR among first responders and evaluate its effectiveness in reducing trauma‐related symptoms; a secondary aim was to identify whether EMDR has been used as an early intervention for this cohort and determine its effectiveness as such. Four databases were searched. Studies were included if they evaluated the extent to which EMDR was effective in alleviating symptoms stemming from work‐related trauma exposure among first responders. The findings from each study were reported descriptively, and eight studies that evaluated the efficacy of EMDR in this population were included. There was substantial variation in how EMDR was implemented, particularly in the type, duration, frequency, and timing. The findings suggest that EMDR can alleviate symptoms of work‐related trauma exposure among first responders; however, findings regarding early intervention were inconclusive, and a methodological quality assessment revealed that all studies were classified as being of either weak or medium quality. Although this review provides preliminary insights into the effectiveness of EMDR for first responders, the conclusions that can be drawn from the literature are limited, and the findings highlight several gaps in the literature.